An Engineered Pseudo‐Macrophage for Rapid Treatment of Bacteria‐Infected Osteomyelitis via Microwave‐Excited Anti‐Infection and Immunoregulation. Issue 41 (15th August 2021) - Fu, Jieni; Li, Yuan; Zhang, Yu; Liang, Yanqin; Zheng, Yufeng; Li, Zhaoyang; Zhu, Shengli; Li, Changyi; Cui, Zhenduo; Wu, Shuilin
Abstract: Preventing deep bacterial infection and simultaneously enhancing osteogenic differentiation are in great demand for osteomyelitis. Microwave (MW) dynamic therapy is attracting attention due to its excellent penetration ability, but the mechanism of MW‐induced reactive oxygen species (ROS) is still unknown. Herein, MW‐responsive engineered pseudo‐macrophages (M‐Fe3 O4 /Au nanoparticles (NPs)) are fabricated to clear Staphylococcus aureus infections and induce M2 polarization of macrophages to improve osteogenic differentiation of bone marrow mesenchymal stem cells (MSCs) under MW irradiation. Fe3 O4 /Au NPs can generate · O2 − and heat under MW irradiation in a saline solution, and the mechanism is put forward via finite element modeling and density functional theory calculations. Due to the gap plasmon, electromagnetic hotspots are produced at Fe3 O4 –Au interface at 2.45 GHz. Because of these induced electromagnetic hotspots, the sodium species is field‐ionized and subsequently reacts with oxygen to produce · O2 − . Meanwhile, the Fe3 O4 /Au NPs have a stronger ability than Fe3 O4 NPs to fix oxygen, favoring the production of ROS. Additionally, MW‐treated macrophages diminish to secrete inflammatory cytokines, resulting in the decrease of ROS production in MSCs and thus enhancing their osteogenic differentiation. These engineered pseudo‐macrophages will be promising for effectively treating bacterial infections and promoting osteoblast differentiation simultaneously in deep tissues under MW irradiation. Abstract : Engineered pseudo‐macrophage M‐Fe3 O4 /Au therapeutic nanoparticles (NPs) that can be locally accumulated at infection sites through double targeting of proteins and magnets and that can mitigate the inflammatory response by immunoregulation through an electromagnetic field produced by microwave (MW) irradiation and neutralizing inflammatory cytokine, are developed; the Fe3 O4 /Au NPs can generate O2 − and heat by MW assistance.